2019
DOI: 10.1097/adm.0000000000000553
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study of an Integrated Smartphone and Breathalyzer Contingency Management Intervention for Alcohol Use

Abstract: Introduction: Monitoring devices provide a platform for assessing alcohol use and implementing alcohol interventions. This pilot study focused on assessing the early-stage feasibility and usability of a smartphone-based application and breathalyzer used in a contingency management intervention for alcohol use. Methods: Six non-treatment seeking participants completed a 9-week ABA within-subjects designed intervention targeting alcohol use. Participants submitted 2-8 alcohol breathalyzer samples per day and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
(27 reference statements)
2
17
0
Order By: Relevance
“…In addition, the study reported large differences in the percentage of negative samples in CM (85%) versus control (35%) participants ( n = 40). These results are consistent with several other studies that have employed technology‐based CM procedures to promote abstinence from alcohol (Alessi & Petry, 2013; Oluwoye et al, 2019). A recent feasibility study also extended technology‐based CM to promote abstinence from cannabis (Beckham et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the study reported large differences in the percentage of negative samples in CM (85%) versus control (35%) participants ( n = 40). These results are consistent with several other studies that have employed technology‐based CM procedures to promote abstinence from alcohol (Alessi & Petry, 2013; Oluwoye et al, 2019). A recent feasibility study also extended technology‐based CM to promote abstinence from cannabis (Beckham et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Technology might optimise the application of reinforcement principles, monitoring and reinforcing the target behaviour more frequently than is otherwise possible [22,24]. A meta-analysis of mobile telephone-delivered CM [25] and more recent evaluation studies [19,[26][27][28][29][30] suggest these interventions are effective in generating positive behaviour change. However, the platforms upon which these interventions can be implemented might vary in their appropriateness or acceptability to the patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Once the modifications are made in response to the second wave of clinician feedback, ARMS will be evaluated primarily for efficacy but also for feasibility and patient usability through an A-B-A (or, "return-to-baseline") completely within-subject experimental design. Following similar single subject-design studies conducted by our group [20,24], the two A phases will each last 2 weeks and the B phase will last 4 weeks, for a total study duration of 8 weeks. During all phases, participants will be asked to use the ARMS app to submit breathalyzer samples at 10 AM, 2 PM, and 8 PM each day.…”
Section: Methodsmentioning
confidence: 99%
“…Fortunately, recent technological advances have enabled the combined use of mobile apps and low-cost consumer electronic breathalyzer devices to remotely monitor alcohol use [17,18]. Studies wherein smartphone apps and remote breathalyzers were used to provide contingency management for AUD have found them to be effective in promoting alcohol abstinence [17,19,20]. Although other technologies, such as prescription digital therapeutics (eg, reSET and reSET-O by Pear Therapeutics), have been approved by the US Food and Drug Administration (FDA) for substance use disorders, they have not directly targeted substance abstinence.…”
Section: Introductionmentioning
confidence: 99%